Protective effects of Descurainia sophia seeds extract and its fractions on pulmonary edema by untargeted urine and serum metabolomics strategy - Zhang, Jinying; Zhou, Ning; Wang, Yongxiang; Liu, Tong; Cao, Yumin; Feng, Weisheng; Zheng, Xiaoke (Frontiers in Pharmacology, 2023)
Background: Descurainia sophia seeds (DS) is a well-known traditional Chinese medicine (TCM) for treating lung diseases including edema, asthma and cough. Previous pharmacological studies have preliminarily proved DS and its five fractions from different polar parts could alleviate pulmonary edema (PE) in some way. However, the underlying mechanism remains unclear. The study aimed to further evaluate therapeutic effect of DS and its five fractions on PE and investigate potential mechanism through urine and serum metabolomics. Methods: A PE model was established by intrapleural injection of carrageenan (CAR). Rats were pretreated with DS and its five fractions (polysaccharides, DS-Pol; oligosaccharides, DS-Oli; flavonoid glycosides, DS-FG; flavonoid aglycone, DS-FA; fat oil fraction, DS-FO.) for 7 consecutive days. After 48 hours of CAR injection, lung tissues were subjected to histopathological assessment. Urine and serum metabolomics were performed by UHPLC-Q/TOF-MS, respectively. Principal component analysis (PCA) and orthogonal partial least squares-discriminant analysis (OPLS-DA) were operated for metabolic profiles of rats and potential biomarkers related to treatment. Heat maps and metabolic network were constructed to deeply explore the mechanism of DS and five fractions against PE. Results: DS and its five fractions could attenuate lung pathological injury in different degrees and DS-Oli/DS-FG/DS-FO had a more remarkable effect among fractions. Moreover, DS-Oli/DS-FG/DS-FA/DS-FO could regulate metabolic profiles of PE rats, but DS-Pol fraction performed slightly worse. In metabolic pathways analysis, the five fractions could improve PE to some degree due to their anti-inflammation, immune regulation and kidney protection activities by mediating taurine and hypotaurine metabolism, tryptophan metabolism and arachidonic acid metabolism; but DS-Oli/DS-FG/DS-FO fractions played more important role in edema fluid reabsorption, reduction of vascular leakage through regulating phenylalanine metabolism, glycerophospholipid metabolism etc. Heat maps and HCA further indicated DS-Oli/DS-FG/DS-FO were better than DS-Pol/DS-FA in PE. Therefore, the five fractions played a synergistic effect on PE from different aspects, thus constituting the entire efficacy of DS. Thereinto, DS-Oli/DS-FG/DS-FO fractions could be used as an alternative of DS. Conclusion: The metabolomics approach combined with split fraction of medicine herbs proved the role of five DS fractions in treating PE, providing a novel insight into the action mechanism study of TCM.